Inside Putin's Russia - Jack, Andrew, 1967- (Oxford ; New York : Oxford University Press, 2006)
"International views of Russia have changed drastically in the last decade, due in part to the leadership of the decidedly pro-Western President Yeltsin. It was not without concern that we saw the next elected leader pulled from the ranks of the former KGB. Andrew Jack, former Moscow bureau chief for the Financial Times, uses in-depth research and years of journalistic experience to bring us the first full picture of Vladimir Putin. Jack describes how Putin grew to become the most powerful man in Russia, defying domestic and foreign expectations and presiding over a period of strong economic growth, significant restructuring, and rising international prestige. Despite criticism of his handling of the war in Chechnya and of the controls he introduced on parliament and the media, Putin has united Russian society and maintained extraordinarily high popularity. Inside Putin's Russia digs behind the rumors and speculation, illuminating Putin's character and the changing nature of the Russia he leads. It highlights some of the more troubling trends as he consolidates his leadership during a second presidential term marred by the Beslan tragedy, the attacks on Yukos, and Russian policy towards Ukraine. Now with a new Epilogue by the author, this invaluable book offers important insights for anyone interested in the past, present, and future of Russia."--Page 4 of cover.
In the Kremlin library -- Coming to terms -- The man from nowhere -- Prisoner of the Caucasus -- Shooting the messenger -- Autumn of the oligarchs -- The price of reform -- A bridge too far -- Towards liberal authoritarianism.
"First published in Great Britain by Granta Books 2004"--Title page verso.
Includes index.
Keywords: Putin, Vladimir Vladimirovich, -- 1952-; Poutine, Vladimir Vladimirovitch, -- 1952-; Putin, Vladimir Vladimirovich, -- 1952-; Since 1991; Politics and government; Russia (Federation) -- Politics and government -- 1991-; Russie -- Politique et gouvernement -- 1991-2000.; Russie -- Politique et gouvernement -- 2000-; Russia (Federation)